Global Supply Chain Disruptions and Their Impact on the World’s Maritime Shipping and Ports - Andrzej S. GRZELAKOWSKI (Communications of International Proceedings, 2021)
The crisis caused by the Covid-19 pandemic has triggered extensive disruptions in all links in the global supply chains. These disruptions hit particularly hard container shipping and terminals. This study attempts to determine the causes and consequences of disruptions in the global supply chains and to indicate the extent of these disruptions in the maritime sector.  The main research objective is to assess the impact of the Covid-19 crisis on the global supply chains operations and to determine to what extent the disruptions disorganized the world trade and maritime transport. The author attempts to answer the research questions: 1/ whether maritime transport is one of the main reasons for the continuous disruptions in the supply chains, 2/ or the reasons for their current inefficiency can be found in other links. The research carried out is based on the analysis of many reports and publications as well as numerous interviews conducted by the author with the representatives of the shipowners and port sector. The obtained research results indicate that:  1/ container shipping and port container terminals are particularly vulnerable and not very resistant to any disruptions in the global supply chains, 2/ the accumulation of disruptions in this link with the disruptions in other segments of the supply chains leads to transferring the first ones onto the other, 3/ it is necessary to change the current model of supply chain operations and management, transforming the currently dominant, simple supply chains into smart, circular economy supply chains.
Keywords: Global supply chain management; supply chain disruptions; global maritime transport markets; port container terminal congestion.